Redirection of the Transcription Factor SP1 to AT Rich Binding Sites by a Synthetic Adaptor Molecule. Issue 9 (24th August 2021) - Bolz, Mathias; Scheffer, Ute; Kalden, Elisabeth; Göbel, Michael W.
Abstract: The ubiquitous transcription factor SP1 binds to a GC rich consensus sequence. Here we describe an adaptor molecule that mediates binding of SP1 to a non‐cognate DNA site rich in AT. The adaptor is comprised of a Dervan ‐type hairpin polyamide with high affinity to an AT rich hexamer duplex. It also carries a 27mer DNA that contains the SP1 consensus sequence. The synthesis and purification of the polyamide‐DNA conjugate is reported. Pulldown experiments and western blot analysis demonstrate adaptor mediated binding of SP1 to the hexamer duplex TTGTTA. Abstract :